Family doctors role in the early diagnosis of lungs cancers - Romatowska-Dziób, Hanna; Kiss, Bogumił (Przewodnik Lekarza/Guide for GPs, 2005)
An increase in the incidence of lung cancer has decided about the image of malignant neoplasm in all developed countries in XX century. The development and death rate caused by malignant lung tumour among about 65-year-old patients has recently reached the highest, never-recorded level in Poland. The diagnosis of lung cancer does not necessarily mean a patient’s death as the fate of a person who suffers from lung cancer depends on proper diagnosis made during the first appointment usually with the family doctor. Neglecting or underestimating the symptoms reported by patients or their families means huge delay in taking a decission to have proprer tests. As a result it is too late to start effective treatment after the diagnosis has already been taken. Each family doctor deals with 3-10 new neoplasm casualties every year. Statistics indicate that 30% of patients lose approximately 4.5 months as a result of wrong medical tests and diagnosis. In such situations it is adviseable to omit “indirect levels”, where the ill can be subjected to uneffective attempts of observation or treatment without having undregone particular and deliberate examinations. Repeating and illogical expanding of further medical tests that do not contribute any significant factors to the diagnosis not only prolongs the observation period and worsens the patient’s chances to recover but also increases the expenses. Professional diagnosis of cancerous disease should be made only on the basis of co-operation of family doctors, clinicians, radiologists and pathomorphologists. Lung cancer shows high heterogeneity, as only 30-40% of this kind of cancer show texture of only one histological type. From practical point of view while considering the choice of treatment method, the most important thing is to distinguish microcellural (inoperable) cancer from the other types of cancer. Among the possibilities of prevention from the growth and development of lung cancer, whose the forefront is taken by the primary prevention, is the elimination of smoking which is responsible for the growth of 80-90% of all cases affected by this sort of tumour. These are family doctors who take responsibility for the level and results of oncological treatment that are reached by a certain country